Nature: Shaped by Water (Symphony in the Flint Hills, 2018)
Introduction: For thousands of years, waves of cultures crossed the seemingly timeless plain — by foot or prairie schooner — unaware of its ancient past. The metaphor of “rolling heaves of the prairie” as swelling waves took on new meaning when science proved that this great Sea of Grass was once the bed of a shallow ocean teeming with corals, clams, and sponges. The prairie landscape had long secreted clues to its genesis, with springs, rivers, caves, and waterfalls channeling through limestone forged from the shell and bone of primordial sea life.